"Emad-Sara Transform" a new integral transform. Issue 7 (3rd October 2021) - Maktoof, Sara Falih; Kuffi, Emad; Abbas, Elaf Sabah
Abstract: In this paper, a new integral transformation named "Emad-Sara Transform" has been proposed to solve linear ordinary differential equations with constant coefficients.